Commonalities and differences in set-up and data collection across European spondyloarthritis registries - results from the EuroSpA collaboration - Linde, Louise; Ørnbjerg, Lykke M; Rasmussen, Simon H; Love, Thorvardur Jon; Loft, Anne Gitte; Závada, Jakub; Vencovský, Jiří; Laas, Karin; Nordstrom, Dan; Sokka-Isler, Tuulikki; Gudbjornsson, Bjorn; Gröndal, Gerdur; et al. (Arthritis research & therapy, 2023)
BACKGROUND: In European axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA) clinical registries, we aimed to investigate commonalities and differences in (1) set-up, clinical data collection; (2) data availability and completeness; and (3) wording, recall period, and scale used for selected patient-reported outcome measures (PROMs). METHODS: Data was obtained as part of the EuroSpA Research Collaboration Network and consisted of (1) an online survey and follow-up interview, (2) upload of real-world data, and (3) selected PROMs included in the online survey. RESULTS: Fifteen registries participated, contributing 33,948 patients (axSpA: 21,330 (63%), PsA: 12,618 (37%)). The reported coverage of eligible patients ranged from 0.5 to 100%. Information on age, sex, biological/targeted synthetic disease-modifying anti-rheumatic drug treatment, disease duration, and C-reactive protein was available in all registries with data completeness between 85% and 100%. All PROMs (Bath Ankylosing Spondylitis Disease Activity and Functional Indices, Health Assessment Questionnaire, and patient global, pain and fatigue assessments) were more complete after 2015 (68-86%) compared to prior (50-79%). Patient global, pain and fatigue assessments showed heterogeneity between registries in terms of wording, recall periods, and scale. CONCLUSION: Important heterogeneity in registry design and data collection across fifteen European axSpA and PsA registries was observed. Several core measures were widely available, and an increase in data completeness of PROMs in recent years was identified. This study might serve as a basis for examining how differences in data collection across registries may impact the results of collaborative research in the future.
Keywords: Spondylitis, Ankylosing; psoriatická artritida; Pain; Registries; ankylózující spondylitida; Arthritis, Psoriatic; Spondyloarthritis; lidé; Clinical data collection; Collaborative research; spondylartritida; registrace; Humans; Spondylarthritis; European registries; bolest; Real-world evidence